Pemanfaatan Kangkung Darat (Ipomoea Reptans Poir) menjadi Abon Kangkung sebagai Pangan Fungsional di Desa Cipareuan Kabupaten Garut - Nurul Aulia Dewi; Mardiana Mardiana (Universitas Malahayati Lampung, 2023)
ABSTRAK Desa Cipareuan memiliki produktivitas budidaya kangkung darat yang cukup tinggi karena lahan penanaman padi dan palawija memanfaatkan sistem tumpang sari yang ditanami kangkung sehingga dapat mengefisiensi lahan dan biaya. Kangkung darat memiliki kandungan karbohidrat 5,4 gram, lemak 0,3 gram, protein 3 gram, energi 29 kal, serat 1 gram, fosfor 50 mg, kalsium 73 gram, vitamin A 6300 IU, besi 2,5 mg, vitamin B1 0,07 mg, vitamin C 32 mg, dan air 89,7 gram. Kangkung merupakan sayuran yang belum dimanfaatkan secara maksimal dan hanya dimanfaatkan sebagai lalapan atau tumis sehingga dilakukan inovasi pengembangan produk menjadi Abon Kangkung. Tujuan pemberdayaan masyarakat Desa Cipareuan adalah memanfaatkan kangkung menjadi produk pangan fungsional inovatif yang dapat memenuhi selera konsumen, memiliki nilai ekonomis dan bermanfaat bagi Kesehatan. Pengabdian kepada Kader PKK dan Posyandu ini dilakukan menggunakan metode penyuluhan pembuatan Abon Kangkung yang dilaksanakan di Desa Cipareuan pada tanggal 13 Agustus 2022. Hasil yang diperoleh setelah penyuluhan, terdapat peningkatan pengetahuan Kader PKK dan Posyandu mengenai pemanfaatan kangkung menjadi produk yang mempunyai nilai gizi dan peluang ekonomi menjanjikan sehingga mampu meningkatkan nilai ekonomi bagi masyarakat di Desa Cipareuan. Kata Kunci: Pemberdayaan Masyarakat, Kangkung Darat, Abon Kangkung, Pangan Fungsional ABSTRACT Cipareuan Village has a fairly high productivity of ground water spinach cultivation because the paddy and secondary crops cultivation utilizes an intercropping system planted with watercress so as to save land and costs. Ground kale contains 5.4 grams of carbohydrates, 0.3 grams of fat, 3 grams of protein, 29 cal of energy, 1 gram of fiber, 50 mg of phosphorus, 73 grams of calcium, 6300 IU of vitamin A, 2.5 mg of iron, 0 vitamin B1. .07 mg, 32 mg of vitamin C, and 89.7 grams of air. Kangkung is a vegetable that has not been used optimally and is only used as fresh vegetables or stir-fried so that product development innovations are carried out to become Shredded Kangkung. The aim of empowering the Cipareuan Village community is to utilize water spinach into innovative functional food products that can meet consumer tastes, have economic value and are beneficial to health. This service to PKK and Posyandu Cadres was carried out using the counseling method for making Shredded Kangkung which was carried out in Cipareuan Village on August 13, 2022. The results obtained after counseling were that there was an increase in the knowledge of PKK and Posyandu Cadres regarding the utilization of kale into products that have nutritional value and opportunities Promising economy so as to be able to increase economic value for the people in Cipareuan Village. Keywords: Community Empowerment, Ground Kangkung, Shredded Kangkung, Functional Food ABSTRACT Cipareuan Village has a fairly high productivity of ground water spinach cultivation because the paddy and secondary crops cultivation utilizes an intercropping system planted with watercress so as to save land and costs. Ground kale contains 5.4 grams of carbohydrates, 0.3 grams of fat, 3 grams of protein, 29 cal of energy, 1 gram of fiber, 50 mg of phosphorus, 73 grams of calcium, 6300 IU of vitamin A, 2.5 mg of iron, 0 vitamin B1. .07 mg, 32 mg of vitamin C, and 89.7 grams of air. Kangkung is a vegetable that has not been used optimally and is only used as fresh vegetables or stir-fried so that product development innovations are carried out to become Shredded Kangkung. The aim of empowering the Cipareuan Village community is to utilize water spinach into innovative functional food products that can meet consumer tastes, have economic value and are beneficial to health. This service to PKK and Posyandu Cadres was carried out using the counseling method for making Shredded Kangkung which was carried out in Cipareuan Village on August 13, 2022. The results obtained after counseling were that there was an increase in the knowledge of PKK and Posyandu Cadres regarding the utilization of kale into products that have nutritional value and opportunities Promising economy so as to be able to increase economic value for the people in Cipareuan Village. Keywords: Community Empowerment, Ground Kangkung, Shredded Kangkung, Functional Food